White Noise Speech Illusions: A Trait-Dependent Risk Marker for Psychotic Disorder? - Schepers, Elaine; Lousberg, Richel; Guloksuz, Sinan; Pries, Lotta-Katrin; Delespaul, Philippe; Kenis, Gunter; Luykx, Jurjen J.; Lin, Bochao D.; Richards, Alexander L.; Akdede, Berna; Binbay, Tolga; Altınyazar, Vesile; et al. (Frontiers in Psychiatry, 2019)
Introduction: White noise speech illusions index liability for psychotic disorder in case-control comparisons. In the current study, we examined i) the rate of white noise speech illusions in siblings of patients with psychotic disorder, and ii) to what degree this rate would be contingent on exposure to known environmental risk factors (childhood adversity and recent life events) and level of known endophenotypic dimensions of psychotic disorder (psychotic experiences assessed with the CAPE scale and cognitive ability). Methods: The White Noise task was used as an experimental paradigm to elicit and measure speech illusions in 1014 patients with psychotic disorders, 1157 siblings and 1507 healthy participants. We examined associations between speech illusions and increasing familial risk (control -> sibling -> patient), modelled both as a linear and a categorical effect, and associations between speech illusions and level of childhood adversities and life events as well as with CAPE scores and cognitive ability scores. Results: While a positive association was found between white noise speech illusions across hypothesized increasing levels of familial risk (controls -> siblings -> patients): OR linear 1.11, 95% CI 1.02-1.21, p =0.019), there was no evidence for a categorical association with sibling status (OR 0.93, 95% CI 0.79-1.09, p =0.360). The association between speech illusions and linear familial risk was greater if scores on the CAPE positive scale were higher (p interaction =0.003; ORlow CAPE positive scale 0.96, 95% CI 0.85-1.07; ORhigh CAPE positive scale 1.26, 95% CI 1.09-1.46) , cognitive ability was lower (p interaction <0.001; ORhigh cognitive ability= 0.94, 95% CI 0.84-1.05; ORlow cognitive ability= 1.43, 95% CI 1.23-1.68) and exposure to childhood adversity was higher (p interaction <0.001; ORlow adversity 0.92, 95% CI 0.82-1.04; ORhigh adversity 1.31, 95% CI 1.13-1.52). A similar, although less marked, pattern was seen for categorical patient-control and sibling-control comparisons. Exposure to recent life events did not modify the association between white noise and familial risk (p interaction=0.232). Conclusion: The association between white noise speech illusions and familial risk is contingent on additional evidence of endophenotypic expression and of exposure childhood adversity. Therefore, speech illusions may represent a trait-dependent risk marker.